African dwarf-crocodile scale-counts evaluated as supporters of Osteolaemus tetraspis osborni (Reptilia, Crocodylia, Crocodylidae) - Van Hoven, Wouter (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.